The symbolic construction of security in the process of creating Flagrant Courts in Costa Rica - Beltrán Conejo, Vanessa (2016)
This article rebuilds the political process that gives rise to the Courts of Flagran-cy in Costa Rica (2008-2009). This research is based on the discourses repro-duced around crime and punishment throughout this process from a qualitative approach. The method of critical discourse analysis is used to deepen the dyna-mics of symbolic power that emerged in the three institutional spaces where the project was discussed: a specialized committee created from the Executive, Full Court of the Judiciary and the security commission established in the Congress for the specific study of this proposal. This process revealed a dominant discour-se on security based on the exercise of punitive power, control and punishment and the reproduction of fear and social alarm as a main discursive nuclei.